2012
DOI: 10.1038/jes.2012.51
|View full text |Cite
|
Sign up to set email alerts
|

Expressing urine from a gel disposable diaper for biomonitoring using phthalates as an example

Abstract: The urinary metabolites of phthalates are well-accepted exposure biomarkers for adults and children older than 6 years but are not commonly used for infants owing to non-convenient sampling. In the light of this situation, a novel sampling method based on monitoring the urine expressed from the gel diaper was developed. The urine was expressed from the gel absorbent after mixing the absorbent with CaCl2 and then collected by a laboratory-made device; the urinary phthalate metabolites were extracted and cleaned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 528 publications
(685 reference statements)
0
10
0
Order By: Relevance
“…There have been no reported data so far to compare with our data on CDCA and 3-PBA concentrations detected from children at this time; only a few research teams have tried to measure the biochemical or xenobiotic markers in urine extracted from used diapers. [16][17][18] One research group has reported the concentration of urinary CDCA in 120 children aged 6 to 12 years to be 0.05 mg/l (median). 11 Becker et al 19 reported that the geometric mean of urinary 3-PBA concentrations in children aged between 2 and 5 years was 0.34 mg/l.…”
Section: Application Of Methods To Used Diaper Samplesmentioning
confidence: 99%
“…There have been no reported data so far to compare with our data on CDCA and 3-PBA concentrations detected from children at this time; only a few research teams have tried to measure the biochemical or xenobiotic markers in urine extracted from used diapers. [16][17][18] One research group has reported the concentration of urinary CDCA in 120 children aged 6 to 12 years to be 0.05 mg/l (median). 11 Becker et al 19 reported that the geometric mean of urinary 3-PBA concentrations in children aged between 2 and 5 years was 0.34 mg/l.…”
Section: Application Of Methods To Used Diaper Samplesmentioning
confidence: 99%
“…The main reason for this data gap can be linked to the infants’ and toddlers’ immaturity of bladder control, which makes urine sampling challenging. Diapers could, therefore, be a valid alternative collection medium among children in this age group [ 37 ]. There are not many biomonitoring studies to date that use diapers as a collection medium for the urine of non-toilet-trained children.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in this sampling technique has grown, and a few studies have been published in this regard. In particular, urine extracted from diapers has been used to investigate the exposure of children to organophosphate insecticides [ 39 ], neonicotinoid insecticides [ 40 ], pyrethroid insecticides [ 41 ], tebuconazole [ 42 ], and phenolic endocrine disruptors [ 43 ] such as bisphenol A, bisphenol A analogs [ 44 ], triclosan, and phthalates [ 37 ]. These studies outlined several advantages on the use of diapers to collect urine in order to perform large surveys of young populations.…”
Section: Introductionmentioning
confidence: 99%
“…The total amount of free and glucuronide-conjugate BPs was extracted from samples by enzymatic deconjugation followed by Solid Phase Extraction (SPE) according to Hu et al [ 58 ]. For each sample, the solution extracted from the diapers was buffered at pH 5.5–6 with ammonium acetate, then treated with 80 ÎĽL of β-glucuronidase to hydrolyze the glucuronide conjugates, and kept overnight at 37 °C [ 57 , 59 ]. BPs were extracted and purified using a SPE-offline protocol based on Chromabond Easy column (3 mL, 200 mg, Macherey-Nagel) [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a first step in understanding BP exposure among children, we analyzed 15 bisphenols (bisphenol A, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol P, bisphenol PH, bisphenol S, bisphenol TMC, and bisphenol Z) in urine extracted from diapers of infants and toddlers [ 55 , 56 ] attending Swiss daycare centers. Urine extracted from used diapers is a reliable sampling procedure, and sufficient quantities of urine can be obtained for the chemical analytical methods [ 57 , 58 , 59 ]. This sampling approach allowed us to investigate internal BP dose distributions in this young population at risk.…”
Section: Introductionmentioning
confidence: 99%